Penerapan Metode Discovery Learning untuk Meningkatkan Prestasi Belajar Fisika Materi Listrik Arus Searah Pada Siswa Kelas XII MIPA 3 Tahun Pelajaran 2019/2020 - Nelda Roza (Journal on Education, 2020)
There were problems related to student achievement in class XII MIPA 3 so it is necessary to find a solution through a study. The purpose of this research was to improve the physics learning achievement of direct current electric material in class XII MIPA 3 academic year 2019/2020 through the application of the discovery learning method. The research was conducted in Class XII of SMAN 2 Siak Hulu. Implementation time is from July to September 2019. Based on the results of learning activities Direct Current Electrical Material physics that have been carried out for three cycles, and based on all the discussions and analyzes that have been carried out, it can deactivate the Physics learning of Direct Current Electricity material by active learning. positive impact in increasing student achievement overcoming the increase in student learning completeness in each cycle, namely cycle I (60%), cycle II (73%), cycle III (90%). The application of the active learning method of the Discovery Learning method in Physics subjects has a positive effect, namely it can increase student motivation as indicated by the average student's answer which states that students are interested and interested in learning models so that they become motivated to learn. The application of the active learning method of the Discovery Learning method in Physics subjects can improve mastery of Physics subjects with the subject of Direct Current Electricity and understanding the meaning contained therein.